2016
DOI: 10.1002/jbm.b.33629
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin-loaded electrospun nanocomposite membranes for dental applications

Abstract: Electrospun nanocomposite matrices based on poly(ε-caprolactone) (PCL), nano-hydroxyapatite (nHAp) and amoxicillin (AMX) were designed and investigated for dental applications. nHAp provides good biocompatibility, bioactivity, osteoconductivity, and osteoinductivity properties, and AMX, as antibiotic model, controls and/or reduces bacterial contamination of periodontal defects while enhancing tissue regeneration. A series of polymeric nanocomposites was obtained by varying both the antibiotic and nHAp contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 43 publications
(44 reference statements)
5
36
0
Order By: Relevance
“…Sequential electrospinning to fabricate FGM (Bottino et al, 2011) and coaxial electrospinning to construct core-shell structure (Tang et al, 2016) were utilized to incorporate MNZ into nanofibers for better drug delivery. Additionally, multiple drugs were added into nanofibers in attempts to assist periodontal regeneration, including ampicillin (Schkarpetkin et al, 2016), amoxicillin (Furtos et al, 2017), tetracycline hydrochloride (Ranjbar-Mohammadi et al, 2016), doxycycline hydrochloride (Debridement, 2016), and tinidazole (Khan et al, 2017), etc.…”
Section: Nano-composite Electrospun Fibers In Periodontal Regenerationmentioning
confidence: 99%
“…Sequential electrospinning to fabricate FGM (Bottino et al, 2011) and coaxial electrospinning to construct core-shell structure (Tang et al, 2016) were utilized to incorporate MNZ into nanofibers for better drug delivery. Additionally, multiple drugs were added into nanofibers in attempts to assist periodontal regeneration, including ampicillin (Schkarpetkin et al, 2016), amoxicillin (Furtos et al, 2017), tetracycline hydrochloride (Ranjbar-Mohammadi et al, 2016), doxycycline hydrochloride (Debridement, 2016), and tinidazole (Khan et al, 2017), etc.…”
Section: Nano-composite Electrospun Fibers In Periodontal Regenerationmentioning
confidence: 99%
“…Schneider et al [26] electrospun tricalcium phosphate nanoparticles into poly(lactic-co-glycolic acid) (PLGA) scaffolds, looking at a single concentration of silver, but did not investigate mammalian toxicity of the scaffold. Furtos et al [27] electrospun a PCL scaffold to contain both nHA and amoxicillin, which they tested against four bacterial strains and found that increasing the nHA content reduced the loading efficiency of the antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to avoid bacterial and fungal diseases are important in the oral-facial field. 40 For this reason, scaffolds containing antibiotics have been increasingly used in oral studies 22,27,37,40,49,51 and mucoadhesion strategies are also reported. 83,84 The presence of anti-inflammatory agents in such composites could activate a signaling cascade and trigger the healing process.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…PCL was used in association with alginate for drug release during dental treatments to prevent bacterial accumulation at the site of implantation. 22 PCL has been also used in drug delivery for creation of membranes incorporating nano-hydroxyapatite and amoxicillin, 27 obtaining good biocompatibility and reducing bacterial contamination of periodontal defects. Further applications were described for TE.…”
Section: Pclmentioning
confidence: 99%